Application of the SBA method to solving optimal control problem governed by systems of nonlinear partial differential equations - Abbo, Bakari; Pare, Youssouf; Francis, Bassono; Choroma, Marayi; Some, Blaise (International Journal of Advanced Mathematical Sciences, 2013)
In this article, we are interested in solving optimal control problemsgoverned by a system of nonlinear partial di¤erential equations by the itera-tive method SBA (combination of the Adomian method, successive approx-imations method and the principle of Picard )[17].This technique allows toreduce the problem of optimal control of the error function in a classical minimization problem.